Adaptation to climate change: ethnic groups in Southwest China. (15th March 2022) - Yang, Hua; He, Jun; Su, Yufang; Xu, Jianchu
ABSTRACT : Based on interviews with 1216 randomly selected households in Yunnan, Southwest China, we assessed local people's perceptions and coping strategies on climate change, and determined its influencing factors. Results indicated that 72% of the respondents perceived climate change-associated impacts, while 82% and 85% perceived the changes in temperature and precipitation, respectively. Most respondents perceived climate warming and decreases in precipitation. Drought and erratic rainfall are the most serious impacts. Approximately 40% of respondents who perceived climate change have chosen to do nothing. Others have reacted by migrating for work, introducing new crop types, giving up planting certain crops, and investing in irrigation infrastructure. The perception and response strategies of local residents to climate change were mainly influenced by the factors related to geographical characteristics and residents' livelihoods. There are significant differences in perception of climate change among Tibetan, Yi and Naxi, while no significant differences in response strategies have been found among ethnic minorities. An integrated programme combining indigenous knowledge with scientific technology and government policies is proposed to enhance the adaptive capacity to climate change of ethnic populations in mountain areas. The policy implications call for understanding of cultural difference that affect people's perception and adaptation to climate change.